Meniscus Segmentation and Tear Detection in the Knee MR Images by Fuzzy c-Means Method - Saygili, Ahmet; Albayrak, Songul (IEEE, 2017)
Computer-assisted diagnosis (CAD) studies on medical images have gained momentum recently. The studies in this area facilitates the work of medical specialists and reduces the time cost. In this study, meniscus segmentation and meniscus tears were performed on 10 different knee MR images in the 3-D DESS standard obtained on the sagittal plane. The morphological operations used in image processing are utilized in the preprocessing stage for segmentation and tear detection. The fuzzy c-means (FCM) method was used to segment the knee joint meniscus tissues and to detect tears. It has been noted that the MR images selected from the meniscus tears differ from each other according to their structures. The next phase of this study will be automatically classified the meniscus according to the types of tears.
Keywords: Medical Image Processing; Meniscus; FCM-Fuzzy C-Means; Meniscus Tears; Medical Segmentation; SYSTEM; Acoustics; Computer Science; Engineering; Telecommunications